Analisis Penerapan Website Dalam Meningkatkan Partisipasi Anggota Koperasi Dewi Sri Bandung - Sudewa , Jaka; Kahar Suputra, I Gede; Ahmad S , Ginanjar (Universitas Koperasi Indonesia, 2024)
The current development of the internet has an influence on business activities, both in the form of companies and independent businesses. One application that can support business activities in increasing sales is by implementing a website, as well as the Dewi Sri Bandung Cooperative in an effort to increase member participation has implemented a website. This research aims to analyze the extent to which the level of effectiveness of implementing the website can be accepted and adapted by users who utilize Cooperative services, especially members and employees. From the results of the research, it can be concluded that the level of effectiveness of website implementation at the Dewi Sri cooperative based on the results of respondents' answers from the questionnaire can be concluded that the implementation of website use can be said to be good, however there is a visible gap between reality and expectations, this indicates that the implementation of website use still has perceived shortcomings. by members, such as errors that often appear in the website application and time efficiency that is not adequate to what the cooperative expects. Even though there are still shortcomings, the implementation of the website that has been carried out so far has had a good impact on participation thereby increasing income at the Dewi Sri Cooperative.